Comparison of Physicochemical and Sensory Properties between Cholesterol-removed Gouda Cheese and Gouda Cheese during Ripening - Jung, Ho-Jung (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
This study was performed to compare physicochemical and sensory properties of cholesterol-removed Gouda cheese (CRGC) and Gouda cheese made in the laboratory during ripening. Composition, short-chain free fatty acids (SCFFA), texture, color, and sensory properties were measured. In chemical composition analyses, moistures were significantly different between control cheeses (42.86%) and sample cheese (48.32%) (p<0.05). But fat and protein in the control and the sample were 32.77, 22.45 and 31.35, 20.39%, respectively, and were not significantly different (p>0.05). The amount of cholesterol in control was 82.52 mg/100 g and the percentage of cholesterol removal was 90.7%. SCFFA increased gradually during ripening and its level of CRGC increased and significantly different from that of control (p<0.05). The texture, hardness, gumminess, and chewiness were significantly increased, but cohesiveness and springiness were not increased in both cheeses during ripening periods (p>0.05). In comparison of the control and sample cheeses, hardness, and springiness were not significantly different, but cohesiveness, gumminess, and chewiness were different (p<0.05). In color measurement, all color values were not different between CRGC and control (p>0.05). However, L* value decreased, while a* and b* values tended to increase significantly (p<0.05). In sensory properties, appearance, aroma, flavor and taste, and texture were significantly increased except buttery and nutty in aroma and sweetness in taste in both cheeses, and were not significantly different between the control and sample cheeses during ripening (p>0.05). Therefore, this study suggests that the quality of cholesterol-removed Gouda cheese is not different from the control cheese.